Geomicrobiology: Molecular and Environmental Perspective - Loy, Alexander; Mandl, Martin; Barton, Larry L. (Springer Netherlands : Imprint: Springer, 2010)
This book is an interdisciplinary review of recent developments in topics including origin of life, microbial-mineral interactions, and microbial processes functioning in marine and terrestrial environments. A major component of this book addresses molecular techniques to evaluate microbial evolution and assess relationships of microbes in complex, natural communities. The function of microbial community members and their possible geological impact are evaluated from a perspective of (meta)genomics, (meta)proteomics, and isotope labeling. As well as summarizing current knowledge in various areas, it also reveals unresolved questions that require future investigations. These chapters enhance our fundamental knowledge of geomicrobiology that contributes to the exploitation of microbial functions in mineral and environmental biotechnology applications. Authors have provided skillful reviews and outlined unique perspectives on environmental microorganisms and their related processes.